2010
DOI: 10.1016/j.biomaterials.2010.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Modified Gellan Gum hydrogels with tunable physical and mechanical properties

Abstract: Gellan Gum (GG) has been recently proposed for tissue engineering applications. GG hydrogels are produced by physical crosslinking methods induced by temperature variation or by the presence of divalent cations. However, physical crosslinking methods may yield hydrogels that become weaker in physiological conditions due to the exchange of divalent cations by monovalent ones. Hence, this work presents a new class of GG hydrogels crosslinkable by both physical and chemical mechanisms. Methacrylate groups were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
335
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 370 publications
(344 citation statements)
references
References 49 publications
7
335
1
1
Order By: Relevance
“…Gellan gum exhibits poor solubility at low temperature, while sufficient gum dissolution with random coil conformation forms uniform gellan gum solutions at temperatures higher than 90°C [39]. Upon temperature decrease, randomly dispersed gellan gum coils adopt a double-helical structure through ionotropic sol-gel transition, which results in high viscous and firm gellan gum gel formation [26,61]. Details of the gellan gum rheology and a case study of experimental implementations can be found in Chang et al [17,22].…”
Section: Gellan Gum Biopolymermentioning
confidence: 99%
“…Gellan gum exhibits poor solubility at low temperature, while sufficient gum dissolution with random coil conformation forms uniform gellan gum solutions at temperatures higher than 90°C [39]. Upon temperature decrease, randomly dispersed gellan gum coils adopt a double-helical structure through ionotropic sol-gel transition, which results in high viscous and firm gellan gum gel formation [26,61]. Details of the gellan gum rheology and a case study of experimental implementations can be found in Chang et al [17,22].…”
Section: Gellan Gum Biopolymermentioning
confidence: 99%
“…Other work using methacrylated LAGG has shown that the degradation rate (in 0.1 mM NaOH, at 37 °C) can be influenced by the cross-linking 90 mechanism, i.e. physical or combined physical and chemical 58 .…”
Section: Why Consider Gellan Gum?mentioning
confidence: 99%
“…Other strategies involve methacrylation of the GG chain (Fig. 1C) followed by physical and/or chemical 65 cross-linking 58 . These approaches can be used to tune the elastic modulus of GG hydrogels to that comparable with a wide range of human soft tissues such as muscle, liver and cartilage 59 .…”
Section: Why Consider Gellan Gum?mentioning
confidence: 99%
“…Such UV cross-linking approaches were recently highlighted as a promising means of accurately controlling bioprinted scaffolds 123 . Although methacrylated gelatin has been the principal material applied for this purpose to date 136,137 , the methacrylated gellan gums that have so far been photopolymerised whilst confined in a casting mould 37,63,104 could be readily applied in UV-bioprinting. Extending MA-GG into the field of UV-bioprinting presents a new mode of GG biofabrication with significant future potential.…”
Section: Bioprintingmentioning
confidence: 99%